2023
DOI: 10.1038/s41598-022-26884-7
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genomes and comparative analysis of Ligustrum species

Abstract: In this study, we assembled and annotated the chloroplast (cp) genomes of four Ligustrum species, L. sinense, L. obtusifolium, L. vicaryi, and L. ovalifolium ‘Aureum’. Including six other published Ligustrum species, we compared various characteristics such as gene structure, sequence alignment, codon preference, and nucleic acid diversity, and performed positive-selection genes screening and phylogenetic analysis. The results showed that the cp genome of Ligustrum was 162,185–166,800 bp in length, with a circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The cp genomes ranged from 158,221 bp (triploid T. vernicifluum ) to 159,710 bp [ T. vernicifluum and T. succedaneum (Ts)], with a difference in size of 1489 bp. Large variation in LSC length (742 bp) accounted for most of this genome-wide variation, which indicated that variation in genome length appears to be mainly caused by variation in LSC length [ 39 ]. The GC content of the ten Toxicodendron accessions ranged from 37.9-38.0%, which is closely related to species affinity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cp genomes ranged from 158,221 bp (triploid T. vernicifluum ) to 159,710 bp [ T. vernicifluum and T. succedaneum (Ts)], with a difference in size of 1489 bp. Large variation in LSC length (742 bp) accounted for most of this genome-wide variation, which indicated that variation in genome length appears to be mainly caused by variation in LSC length [ 39 ]. The GC content of the ten Toxicodendron accessions ranged from 37.9-38.0%, which is closely related to species affinity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the expansion and contraction of the IR, LSC, and SSC regions are common during evolution and are the main reason for variations in plastome size ( Ravi et al., 2007 ; Downie and Jansen, 2015 ; Daniell et al., 2016 ). Significant contraction of IR region was observed among Linderniaceae species ( Supplementary Figure 2 ), which was also common in Lamiales, such as Gesneriaceae ( Gu et al., 2020 ), Lamiaceae ( Su et al., 2022 ), Oleaceae ( Long et al., 2023 ), Plantaginaceae ( Xie et al., 2023 ), and Scrophulariaceae ( Wang et al., 2022 ). Notably, the IR boundaries did not coincide exactly in the three populations of L. polygonoides , but they had the same plastome size.…”
Section: Discussionmentioning
confidence: 91%
“…Comparative analyses make it easy to identify mutational hotspots in plant due to their highly conservative structure. The presence of mutational hotspots surrounded by conserved sequences serves as the foundation for DNA barcodes commonly utilized in population genetic or phylogenetic research [42].…”
Section: Discussionmentioning
confidence: 99%